Joint interpretation of geophysical field experiments in the danube deep-sea fan, Black Sea. (November 2020) - Bialas, J.; Bohlen, T.; Dannowski, A.; Eisenberg-Klein, G.; Gassner, L.; Gehrmann, R.; Heeschen, K.; Hölz, S.; Jegen, M.; Klaucke, I.; Krieger, M.; Mann, J.; et al.
Abstract: Gas hydrates are naturally-occurring solid compounds of gas and water within almost all sediment-rich continental margins. Due to the large amounts of methane stored in submarine gas hydrates, they might serve as future reservoirs for offshore marine gas production. Assessing the reservoir characteristics requires reliable estimates of both the gas and gas hydrate concentration, which can be best addressed using geophysical and geological investigations. Here, we demonstrate the power of joint interpretation of interdisciplinary geophysical techniques and geological laboratory experiments. Regional 2D multichannel seismic data provide the broad overview of a hydrate-bearing area. High-resolution 2D and 3D seismic reflection data provide detailed images of two working areas, the buried S1 channel-levee system at 1500 m water depth (well within the gas hydrate stability zone) and a slope failure location, located at 665 m water depth (top limit of the hydrate formation) next to the S2 channel. Detailed compressional and shear wave (Vs) velocity-depth models were derived from four component ocean-bottom seismic data, the latter from P- to S-conversion upon reflection. Due to their steep reflection angles, shear wave events result in less resolved Vs models. Nevertheless, in case of a change in elasticity of the sediment matrix due to gas hydrate cementation, shear wave events can be used as an indicator. As such, Vs can give insight into the nature of hydrate formation throughout the GHSZ. We present new developments in the application of common reflection surface, normal-incidence-point tomography and full waveform inversion techniques to enhance model resolution for the seismic data sets. 2D and 3D controlled-source electromagnetic measurements provide volume information of the resistivity-depth distribution models. Electrical resistivity of the sediment formation depends on its porosity and the resistivity of the pore fluid. Gas hydrate and free gas generally have much higher electrical resistivities than saline pore fluid, and can be assessed using empirical relationships if the porosity and pore fluid salinity are known. Calibration with logging data, laboratory experiments on hydrate- or ice-bearing sediments, and resulting velocity and resistivity values, guide the joint interpretation into more accurate saturation estimations. Beyond that, a joint inversion framework supporting forward calculation of specialized geophysical methods at distributed locations is under development. In this paper, we summarize these individual components of a multi-parameter study, and their joint application to investigate gas hydrate systems, their equilibrium conditions and preservation of bottom-simulating-reflectors. We analyze data from two working areas at different locations and depth levels along the slope of the Danube Fan, which are both characterized by multiple bottom simulating reflectors indicating the presence of gas hydrate. In the first working area we located two depth windows with indications for moderate 16%–24% gas hydrate formation, but no vertical gas migration. In the second working area we observed fluid migration pathways and active gas seepage, limiting gas hydrate formation to less than 10% at the BSR. Some discrepancies remain between seismic-based and electromagnetic-based models of gas and gas hydrate distribution and saturation estimates, indicating that further in-situ investigations are likely required to better understand the gas hydrate systems at our study areas and to calibrate the inversion processes, which will be required for a joint inversion framework as well. Highlights: Joint seismic, CSEM and geochemical estimate of gas and hydrate saturation. Converted shear wave analyses for gas hydrate distribution. Wide angle full waveform inversion. Paleo-BSRs and gas hydrate system in disequilibrium. Numerical framework for joint inversion of multiple geophysical methods.